LA PLANIFICACIÓN Y DISCIPLINA COMO PROCESOS METÓDICOS PARA MEJORAR EL RENDIMIENTO ACADÉMICO - Aragón, J; Albuja M; Burbano E; Sánchez F; Guzmán J (IJRDO- Journal of Educational Research, 2020)
University student achievement is a topic of high interest for higher education institutions, as well as for public and private companies, and especially for society in general. The problem of the low academic performance of university students affects social aspects such as student desertion, professionals who do not meet the profiles and expectations of companies, and therefore unemployment of qualified labor. Obtaining field and bibliographic data, the origins of this problem can be determined and strategies can be proposed to reduce the problem. The research aimed to identify the causes and effects of low student achievement and to propose strategies to minimize it. The study was carried out with 150 engineering students applying surveys, interviews, corroborating with bibliographic information to determine statistical trends. The main causes identified were 35% due to lack of initial training in an individual’s attitude, there was no development of competencies and skills in fundamental planning and discipline knowledge. Strategies are proposed in the training of parents and teachers so that they transmit to the students and improve their skills in the classroom. The fundamental attitudes are leadership, proactivity, adaptability and initiative that will conclude with the application of planning and discipline in the execution of activities for the fulfillment of objectives, consequently an optimal academic performance.